2016
DOI: 10.1002/jor.23265
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes infected intervertebral discs cause vertebral bone marrow lesions consistent with Modic changes

Abstract: Modic type I change (MC1) are vertebral bone marrow lesions adjacent to degenerated discs that are specific for discogenic low back pain. The etiopathogenesis is unknown, but occult discitis, in particular with Propionibacteria acnes (P. acnes), has been suggested as a possible etiology. If true, antibiotic therapy should be considered for patients with MC1. However, this hypothesis is controversial. While some studies report up to 40% infection rate in herniated discs, others fail to detect infected discs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 49 publications
4
64
0
2
Order By: Relevance
“…There has been some clinical evidence that patients with herniated nuclear (nucleus pulposus) disk material infected with anaerobic pathogens in general, and P. acnes in particular, are more likely develop inflammation and edema of the adjacent vertebrae (Modic changes type I) and back pain (Albert et al, 2013; Urquhart et al, 2015). Clinical and animal-based follow-ups are now corroborating the initial findings showing that local P. acnes proliferation causes upregulation of inflammatory markers and disk degeneration consistent with Modic changes (Aghazadeh et al, 2016; Dudli et al, 2016). There is now even first clinical evidence to suggest that bacterial infection of the intervertebral disk with P. acnes and/or Staphylococcus epidermidis may actually precede all other issues as the root cause of disk herniation and associated pathological changes (Rajasekaran et al, 2017).…”
Section: Spondylodiscitis and Back Painsupporting
confidence: 69%
“…There has been some clinical evidence that patients with herniated nuclear (nucleus pulposus) disk material infected with anaerobic pathogens in general, and P. acnes in particular, are more likely develop inflammation and edema of the adjacent vertebrae (Modic changes type I) and back pain (Albert et al, 2013; Urquhart et al, 2015). Clinical and animal-based follow-ups are now corroborating the initial findings showing that local P. acnes proliferation causes upregulation of inflammatory markers and disk degeneration consistent with Modic changes (Aghazadeh et al, 2016; Dudli et al, 2016). There is now even first clinical evidence to suggest that bacterial infection of the intervertebral disk with P. acnes and/or Staphylococcus epidermidis may actually precede all other issues as the root cause of disk herniation and associated pathological changes (Rajasekaran et al, 2017).…”
Section: Spondylodiscitis and Back Painsupporting
confidence: 69%
“…A recently described animal model demonstrates the ability of P . acnes to induce disc degeneration [17, 18]. However, in microbiologic culture data, contamination is difficult to exclude entirely, as P .…”
Section: Discussionmentioning
confidence: 99%
“…For example, some clinical studies have demonstrated that antibiotic therapy targeting the bacteria significantly reduced the low back pain and Modic changes in patients [9, 10]. In addition, inoculation of P. acnes into normal intervertebral discs of rats or rabbits induced severe disc degeneration and Modic changes [11, 12]. For this reason, P. acnes is thought to be involved in a previously undiscovered pathogeny for series of disc diseases.…”
Section: Introductionmentioning
confidence: 99%